2004
DOI: 10.1038/sj.bjc.6602263
|View full text |Cite
|
Sign up to set email alerts
|

Chlorambucil and lomustine (CL56) in absolute hormone refractory prostate cancer: re-induction of endocrine sensitivity an unexpected finding

Abstract: The management of androgen independent prostate cancer is increasingly disputed. Diethylstilbestrol and steroids have useful second-line activity in its management. The value of chemotherapy still remains contentious. This paper reports a phase 2 study of two orally active chemotherapy drugs in patients who are absolutely hormone refractory having failed primary androgen blockade and combined oestrogens and corticosteroids. In total, 37 patients who were biochemically castrate with absolute hormone refractory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…A criticism of the study by Shamash et al (2005), is that the patients were not androgen suppressed during chemotherapy, and therefore responses to the reinduction of hormone therapy may have been due to the growth of androgen-dependent clones. However, two patients with a previous orchidectomy, and therefore castrate during chemotherapy, responded to rechallenge with DES in their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A criticism of the study by Shamash et al (2005), is that the patients were not androgen suppressed during chemotherapy, and therefore responses to the reinduction of hormone therapy may have been due to the growth of androgen-dependent clones. However, two patients with a previous orchidectomy, and therefore castrate during chemotherapy, responded to rechallenge with DES in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Shamash et al (2005) reported on the reinduction of hormone-sensitivity in androgen refractory prostate cancer patients following chemotherapy with lomustine and chlorambucil. In their prospective study, eight out of 17 (47%) patients who were rechallenged with hormonal therapy following the failure of chemotherapy had a prostate specific antigen (PSA) response.…”
Section: Sirmentioning
confidence: 99%
“…All patients received oral chemotherapy with chlorambucil 1 mg kg À1 starting day 1, lomustine 2 mg kg À1 day 1, etoposide 50 mg daily from day 22 -28 and 36 -42, with the cycle repeating every 56 days. This treatment was based on a previously published regimen (Shamash et al, 2005). Patients were biochemically castrate (testosterone o1.5 nmol l À1 or failed maximum androgen blockade (MAB)) before starting the chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous chemotherapy study involving castrate patients AIPC, we anecdotally observed that re-induction of hormone sensitivity was possible if endocrine therapy was stopped during chemotherapy (Shamash et al, 2005). Therefore, a prospective phase II study was designed to investigate this observation.…”
mentioning
confidence: 99%
“…Cabazitaxel has now been approved by the U.S. Food and Drug Administration though many consider the toxicities unacceptable (8,9); alkylating agents have also been used in the management of prostate cancer for many years although no effects on survival have been observed (10,11). In one phase 2 study of intravenous melphalan using 30 mg/m 2 every 4 weeks in 27 patients, there were no objective responses although one quarter received more than 4 months of therapy due to overall disease stabilization (12).…”
Section: Introductionmentioning
confidence: 99%